Correlation of the vertical dimension of occlusion with five distances between facial landmarks among those of Batak Toba ethnicity - Rehulina Ginting; Debora Lovelisa Hinson Simbolon (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: The normal vertical dimension of occlusion (VDO) results in orofacial and temporomandibular joint (TMJ) biomechanical balance. If the VDO changes due to attrition, full edentulism, accidents involving the lower third of the face and even improper denture manufacturing will result in the disruption of mastication, speech and aesthetic functions. Therefore, the right technique is needed to predict the correct VDO. Purpose: To identify the correlation values and regression equation of the VDO for five distances between facial landmarks among people of Batak Toba ethnicity. Methods: This research is an analytical study with a cross-sectional design. A purposive-sampling technique obtained 30 Batak Toba subjects, consisting of 15 males and 15 females aged 19–24 years. The data were analysed by an independent t-test, one-way ANOVA, the Pearson correlation, and linear regression (p<0.05). Results: A significant difference distance in the VDO (p=0.0001, p<0.05) was observed between male subjects (72.96±3.75mm) and female subjects (65.24±5.12mm). A positive and significant correlation was observed between the VDO distance and the facial landmark distances, where the criteria for significant correlation were the RO–Pu distance being {r male=0.723(p=0.02) and female=0.650(p=0.09)} and the OC–RO distance being {r male=0.689(p=0.004) and female=0.615(p=0.015)}; the moderate correlation criteria were the OC–IC distance being {r male=0.476(p=0.045) and female=0.428(p=0.043)}, the E–E being {r male=0.435(p=0.043) and female=0.458(p=0.047)}, and the EH being {r male=0.398(p=0.051) and female=0.414(p=0.051)}. The regression equation for the VDO distance in males is {[22.694 + 0.673 (RO–Pu)], [24.371 + 0.642 (OC–RO} and in females is {[23.017 + 0.616 (RO–Pu)], [21.795 + 0.632 (OC–RO)]}. Conclusion: The distances of RO–Pu and OC–RO have the strongest correlation with the VDO in people of Batak Toba ethnicity.